Humoral immunity and transcriptome differences of COVID-19 inactivated vacciane and protein subunit vaccine as third booster dose in human - Zhang, Yuwei; Yao, Mingxiao; Guo, Xingyu; Han, Shanshan; Zhang, Shu; Zhang, Jinzhong; Jiang, Xiangkun; Wang, Jianxing; Fang, Ming; Wang, Shuang; Pang, Bo; Liu, Xiaolin; et al. (Frontiers in Immunology, 2022)
Against the background of the severe human health and world economic burden caused by COVID-19, the attenuation of vaccine protection efficacy, and the prevalence of variants of concern (VOCs), the third dose of booster immunization has been put on the agenda. Systems biology approaches can help us gain new perspectives on the characterization of immune responses and the identification of factors underlying vaccine-induced immune efficacy. We analyzed the antibody signature and transcriptional responses of participants vaccinated with SARS-CoV-2 inactivated vaccine and protein subunit vaccine as a third booster dose. The results from the antibody indicated that the third booster dose was effective, and that sequential immunization with the protein subunit vaccine as a booster dose induced stronger humoral immune responses than the inactivated vaccine, and might be more effective against VOCs. In transcriptomic analysis, protein subunit vaccine induced more differentially expressed genes that were significantly associated with many important innate immune pathways. Both the homologous and heterologous boosters could increase the effectiveness against COVID-19, and compared with the inactivated vaccine, the protein subunit vaccine, mediated a stronger humoral immune response and had a more significant correlation with the innate immune function module, which provided certain data support for the sequential immunization strategy.